Household Food Insecurity and Early Childhood Health and Cognitive Development Among Children of Immigrants. (April 2018) - Huang, Ying; Potochnick, Stephanie; Heflin, Colleen M.
Food insecurity is negatively related to child development and health. In this study, we use Early Childhood Longitudinal Study–Birth Cohort data to assess the cognitive and health consequences of household food insecurity for children of immigrants compared with children of native-born parents. Results suggest that children of immigrants from food insecure households fare worse than their native peers from food insecure households in health but not in cognitive skills after child and maternal demographic characteristics are taken into account. The remaining health disparity between children in food insecure immigrant households and children in food insecure nonimmigrant households is explained away by immigrant risk and protective factors. Having parents with strong mental health and living in two-parent families partially offset the negative health consequences associated with food insecurity. However, compared with food insecure nonimmigrant children, low socioeconomic risk may exacerbate the negative health consequences of food insecurity among children of immigrants.